Taxpayer Rights and Obligations in Tax Collection According to the General Provisions and Tax Procedures Law (KUP) - Nisa Alifia Siregar; Naziera Al Hadar; M. Ikhwannur; Suaibatul Aslamia; Vivy Cindya (Jurnal Sahabat ISNU SU, 2025)
This study aims to analyze the effectiveness of tax collection mechanisms in the Indonesian tax system and assess the extent to which legal protection for taxpayers is implemented in practice. Tax collection, which is divided into passive and active approaches, has direct implications for public fiscal compliance and state revenue. Although the Law on General Provisions and Tax Procedures (UU KUP) regulates taxpayer rights such as objections, appeals, and reductions in administrative sanctions, various normative and practical barriers remain that create legal uncertainty, especially for small taxpayers. This study also examines the role of external oversight through the Indonesian Ombudsman and the importance of an educational approach in increasing voluntary compliance. The results of this study emphasize the need for a more equitable and transparent reformulation of tax collection policies to create a balance between state interests and the protection of citizens' rights.